The Effect of Relationship Marketing Orientation on Brand Equity (Case Study: Privileged Branches of Sepah Bank in Tehran) - Azar, Nasim Khoshbahar; Mehrani, Hormoz (International Review of Management and Marketing, 2017)
Many of the provided core services by public banks are general, so the banks find it difficult to compete on their core services. Many banks by creating and strengthening closer relationship with customers, implement relationship marketing orientation. The research in terms of method was descriptive survey which has been done in 8 distinct branch of Sepah Bank in Tehran. Sampling method is Stratified random sampling. According to the proposed model for research, relationship marketing has six key components of trust, bonding, relationship, shared values, empathy and reciprocity that their impact on brand equity has formed research hypotheses. In order to test research hypotheses, structural equation modeling was used. The results show that except by bonding and relationship, the impact of other components of brand equity is approved. Keywords: Relationship Marketing, Brand Equity, Customer Loyalty, Sepah Bank. JEL Classifications: M3, M31